The Noisy Counter-Revolution: Understanding the Cultural Conditions and Dynamics of Populist Politics in Europe in the Digital Age - Rensmann, Lars (2017)
Abstract: The article argues for a cultural turn in the study of populist politics in Europe. Integrating insights from three fields - political sociology, political psychology, and media studies - a new, multi-disciplinary framework is proposed to theorize particular cultural conditions favorable to the electoral success of populist parties. Through this lens, the fourth wave of populism should be viewed as a "noisy", anti-cosmopolitan counter-revolution in defense of traditional cultural identity. Reflective of a deep-seated, value-based great divide in European democracies that largely trumps economic cleavages, populist parties first and foremost politically mobilize long lingering cultural discontent and successfully express a backlash against cultural change. While the populist counter-revolution is engendered by profoundly transformed communicative conditions in the age of social media, its emotional force can best be theorized with the political psychology of authoritarianism: as a n